Some Unresolved Issues of Measuring the Efficiency of Pollinators: Experimentally Testing and Assessing the Predictive Power of Different Methods. (13th December 2018) - Sihag, Ram Chander
Abstract : Knowledge of efficiency of pollinators is valuable in the derivation of (i) the degree of mutualism specialization of a flower visitor in the natural plant communities, (ii) the optimum number of pollinators needed for the maximum pollination in a plant population, and (iii) the pollinator risk assessment in the sustainable agriculture. Earlier researchers used many direct and indirect methods for measuring the pollination efficiency (PE) of flower visitors. However, a great ambiguity exists in the usage of this terminology that necessitated its fresh scrutiny. I tested the available three standard methods afresh to find the efficiency of pollinators. These included comparing the (i) number of pollen grains removed and deposited by the visitors; (ii) seed set resulting from a single and the multiple visits of the visitors; and (iii) "pollen transfer efficiency (PTE)" derived from the foraging behavior and abundances of the visitors. Observations were recorded on the visitors of four plant species in an agroecosystem of Northwest India. These plants represented a wide variety of the floral types across the angiosperms. The first two methods, namely, the "number of pollen grains removed and deposited" and the "seed set resulting from a single and the multiple visits, " were appropriate in finding differences between the efficiency ranks of the pollinators of those flowers where the number of deposited pollen grains was less than the number of ovules in the ovary. However, these two methods completely failed in situations where exactly reverse condition of pollen grains and ovules existed. Thus, these two methods of measuring the PE of visitors had limited approach and lacked a universal application over the entire angiosperm taxa. On the other hand, use of "pollen transfer efficiency", derived from the foraging behavior and abundance of the visitors, seemed to have an edge over the other two methods as this was helpful in finding differences between the efficiency ranks of the pollinators of plants in all the three situations tested in this study. However, validation of all the three methods through the plant reproductive potential seemed to be an integral confirmatory step for drawing inferences about the efficiency of pollinators.